The Effect of Carpal Tunnel Release on Neuropathic Pain in Carpal Tunnel Syndrome - Motoki Sonohata; Toshiyuki Tsuruta; Hiroko Mine; Akihiko Asami; Hideki Ishii; Kenji Tsunoda; Masaaki Mawatari (Pain Research and Management)
Purpose. The aim of this study was to determine the risk factors of neuropathic pain (NP) in the patient with carpal tunnel syndrome (CTS) before and after the carpal tunnel release. Materials and Methods. One hundred and two CTS patients were enrolled in the study. The pain score was measured by the visual analogue score. NP was determined by the painDETECT (PD) questionnaire. All subjects were divided into 3 groups at 12 weeks after surgery: an Improved, Unchanged, and Worsened group. The risk factors of worsening NP after surgery were evaluated. Results. We found that 36% and 18% of patients with CTS had neuropathic pain before and 12 weeks after surgery, respectively, and pain was significantly stronger than in those without NP. The PD score of eight hands worsened after surgery. In the “Improved group,” the average age at the surgery was younger and the pain score was lower than in the “Unchanged group.” Conclusions. The surgery was very effective on NP of CTS; however, the PD in 7% of hands worsened after surgery. Risk factors before surgery that predicted worse NP after surgery were found to be a younger age, weaker pain, and the absence of night pain.